MAKNA PEMBANGUNAN KAWASAN PERBATASAN INDONESIA – FILIPINA BAGI MASYARAKAT MIANGAS - Mamintada, Echoristy Jandry (HOLISTIK, Journal Of Social and Culture, 2017)
The border problem is a crucial issue for a country especially if the country geographically has boundaries adjacent to neighboring countries either directly (mainland) or indirect (sea).In 2002, the Indonesian side was shocked by the decision of the International Court of Justice in The Hague on the status of Sipadan and Ligitan islands whose ownership fell to the State of Malaysia. As a result Indonesia lost two outer islands bordering its neighboring countries. As an archipelagic country, Indonesia now has 92 islands bordering neighboring countries such as Malaysia, Singapore, Philippines, Australia, Timor Leste and Papua New Guenia. There are concerns that occurred after the release of the two islands, what about the status of other outer islands will be the same fate with Sipadan and Ligitan islands. One of the islands is Miangas Island which is administratively included in North Sulawesi territory and directly adjacent to territory of Philippine country. To answer the concerns, the local government of Talaud Islands Government and the central government of the Republic of Indonesia began to imply on the island of Miangas by building facilities and infrastructure, especially in supporting border facilities as a symbol of state power over the island.The research method used in this research is descriptive qualitative which is generally used by social sciences one of them is anthropology which focused on phenomenology that is searching meaning in a phenomenon.This study aims to reveal the meaning contained in the development of Indonesia-Philippine border region and to find out whether the development is in accordance with the characteristics of Miangas community itself or just for political purposes by ignoring the condition of the local communityKeywords: Border, Miangas, Development